Bending-Shear Interaction Domains for Externally Prestressed Concrete Girders. (3rd December 2013) - Recupero, Antonino; Granata, Michele Fabio
Abstract : In prestressed concrete structures, the evaluation of the safety level is generally carried out by separating the bending moment strength and the shear force capacity. Actually interaction between bending moment ( M ) and shear force ( V ) can have significant consequences on evaluations in service life, especially when the ultimate limit state (ULS) is considered. In this paper, the M-V interaction is addressed for prestressed concrete girders, in the cases of both bonded and unbonded prestressing tendons. It can be demonstrated, by drawing the interaction domains ( M-V ), that a significant reduction of the safety level has to be considered when shear force is evaluated together with bending moment on the ULS of the cross-section, especially for external prestressing in concrete T-shaped or box sections of bridge girders. Interaction domains allow designers to evaluate and optimize reinforcement ratios, geometric properties of the beam, and effects of shear on the ultimate state. An analytical model, based on the stress field theory, is developed and proposed in this paper. A numerical example is developed and interaction domains are given for an example of a box section with variation in reinforcement ratio and tendon slope. A validation of the presented model is given, by comparing experimental data in the literature with results found using the proposed analytical approach.